Relações filogenéticas na família Balanidae (Leach, 1917) sensu Newman & Ross, 1976 (Crustacea, Cirripedia) - Pitombo, Fabio Bettini (2000)
Since the time of its proposal, the Balanidae has suffered many modifications. It has been reduced and rearranged until it attained its current status. However, its monophyly and relationship have not been phylogenetically examined and the relationships of Balanidae to other groups of Balanoidea have not been established yet. This study was directed to analyze the monophyly of the family and the groups within it. Thirty-three taxa of Balanidae, 9 of Archaeobalanidae, 3 of Pyrgomatidae and 2 of Balanomorphoidea were used in the analysis. Anatomical aspects of soft and hard parts provided 70 characters. The hypothesis of relationship were obtained through PAUP, software packages using Fitch parsimony as the optimization criterion.As a result, 252 trees with 125 steps (ci = 0.728; ri= 0.87) were obtained. The strict consensus tree showed that Pyrgomatidae is the sister group of Balanidae. The genus Balanus appears in different clades and therefore it is non-monophyletic. Striatobalanus appears within Balanidae close to the clade formed by Megabalaninae and Concaviinae. The "Balanus amphitrite" group (sensu Newman, 1976) with Tetrabalanus and Fistulobalanus form a monophyletic group. Some proposals of character evolution and new homology interpretation were made, based on the character-state optimization.